Variability in the volume transport of deep overflow across the 10°S saddle on the ninetyeast ridge - Shanwu Zhang; Fuwen Qiu; Hangyu Chen; Chunsheng Jing (Scientific Reports)
Abstract Deep overflows across the saddles on the Ninetyeast Ridge are vital for sustaining the deep limb of the Indian Ocean meridional overturning circulation. However, the volume transport or temporal variability of these overflows remains largely unknown. Through a 17-month moored record of velocity profiles, the time-averaged volume transport of the overflow across the saddle near 10°S is estimated at 1.3 Sv (1 Sv = 1 × 106 m3/s), with a 95% confidence interval of 0.8–1.6 Sv. The estimated volume transport is close to those values determined from rotating hydraulic theory and early hydrographic observations. The overflow transport exhibits significant variabilities at semiannual (170 days) and intraseasonal (73 days) scales, which are closely correlated with the wind stress curl east of the Ninetyeast Ridge. These variabilities are attributed to vertically propagating Rossby waves originating from wind stress curl-induced Ekman pumping, which is demonstrated via spectral empirical orthogonal function decomposition of numerical model outputs and by ray tracing based on the dispersion relation for baroclinic Rossby waves. This finding highlights that wind-driven variability plays a crucial role in modulating deep currents and associated overflows in the southeast Indian Ocean.